Nucleation driving force for ω-assisted formation of α and associated ω morphology in β-Ti alloys. (October 2018) - Li, Tong; Kent, Damon; Sha, Gang; Liu, Hongwei; Fries, Suzana G.; Ceguerra, Anna V.; Dargusch, Matthew S.; Cairney, Julie M.
Abstract: The structural and chemical changes at ω/β interfaces and the evolution of the morphology of ω in a near-β alloy during isothermal ageing at 573 K were investigated by atom probe tomography and aberration-corrected high-resolution transmission electron microscopy. Ledges and local O enrichment at semi-coherent isothermal ω interfaces are proposed to provide the key driving force for nucleation of ω-assisted α. Following nucleation of α, the morphology of ω evolves from ellipsoidal to rod-like, induced by rapid consumption of ω by α. Graphical abstract: Unlabelled Image